Salmonella enterica subsp. diarizonae Harboring ST233, ST1263, and ST1845 in Children - Zhou, Mingming; Shi, Qiucheng; Zhang, Xiucai; Mei, Lingling; Ye, Yihua; Fang, Chao; Shang, Shiqiang (Frontiers in Cellular and Infection Microbiology, 2021)
Objective: To analyze the molecular epidemiology, resistance and pathogenicity of Salmonella enterica subsp. diarizonae isolated from children. Methods: Whole genome sequencing were carried out, the molecular serotypes, sequence types, resistance genes and virulence genes of S. enterica subsp. diarizonae isolates were analyzed. Antimicrobial susceptibility test was determined by commercialized micro-dilution method. Results: A total of 3 isolates of S. enterica subsp. diarizonae were isolated during 2015 to 2020. The molecular serotypes of the 3 strains were 61:c:z35, 61:l,v:1,5,7:[z57] and 65:k:z, respectively, and the sequence types were ST1845, ST233 and ST1263. All the 3 isolates were susceptible to ceftriaxone, ceftazidime, cefepime, amoxycillin/clavulanic acid, piperacillin/tazobactam, ertapenem, imipenem, levofloxacin and trimethoprim/sulfamethoxazole. No other resistant gene was detected except aac(6')-Iaa. There were no resistant plasmids detected in all the 3 isolates. A total of 76 genes were present in all isolates, containing 49 genes of Type III Secretion System (T3SS) mediated by SPI-1and SPI-2, 13 genes of Adherence (Type 1fimbriae, Agf and MisL related genes), 11 genes of Iron uptake (Yersiniabactin), 2 genes of Magnesium uptake and 1 gene of Typhoid toxin(cdtB). Conclusion: The serotypes and sequence types of S. enterica subsp. diarizonae isolates were rarely reported in children; all the S. enterica subsp. diarizonae isolates were susceptible to detected antibiotics; T3SS, Adherence, Iron uptake, Magnesium uptake and Typhoid toxin were responsible for pathogenicity of the S. enterica subsp. diarizonae isolates in children.